Synthesizing fractal images by means of shift dynamical systems - Valantinas, Jonas; Valantinas, Rokas; Žumbakis, Tomas (Lietuvos matematikos rinkinys, 2003)
In this paper, the adaptation problem of the time escape algorithm to the special class of fractal images (attractors of iterated function systems) and the necessary mathematical context are analysed. A new original idea for the practical implementation of shift dynamical systems, used in synthesizing fractal images (attractors), is proposed.